Assessment of the management of medical waste during the Coronavirus epidemic was occurring in Al-Diwaniyah Hospital - Razaq Rahi Hamlan; Alaa Kadhim Jasim; Atheer Kadhim Ibadi (مجلة علوم ذي قار, 2023)
Medical waste is a global issue because of its detrimental effects on societal safety and the environment.